2008
DOI: 10.1016/j.nuclphysbps.2008.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Messages on Flavour Physics Beyond the Standard Model

Abstract: I present a brief summary of the main results on flavour physics beyond the Standard Model that have been obtained in 2008 by my collaborators and myself at the TUM. In particular I list main messages coming from our analyses of flavour and CP-violating processes in Supersymmetry, the Littlest Higgs model with T-Parity and a warped extra dimension model with custodial protection for flavour violating Z boson couplings. OvertureElementary particle physicists are eagerly awaiting the first messages from the LHC … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 79 publications
(129 reference statements)
0
2
0
Order By: Relevance
“…The unitarity triangle analysis is mainly sensitive to processes that change flavor by two units. Even in the wellstudied rare K and B decays (flavor change by one unit), many examples of new physics that could have passed the unitarity-triangle screen-supersymmetry, little Higgs models with T -parity, and warped extra dimensionscould give large departures [100]. New sources of CP violation and FCNC occur in models that do not enforce minimal flavor violation.…”
Section: )mentioning
confidence: 99%
“…The unitarity triangle analysis is mainly sensitive to processes that change flavor by two units. Even in the wellstudied rare K and B decays (flavor change by one unit), many examples of new physics that could have passed the unitarity-triangle screen-supersymmetry, little Higgs models with T -parity, and warped extra dimensionscould give large departures [100]. New sources of CP violation and FCNC occur in models that do not enforce minimal flavor violation.…”
Section: )mentioning
confidence: 99%
“…The most important result of the present paper are the Feynman rules collected in Appendix D. These rules allowed already to perform two detailed phenomenological analyses of ∆F = 2 FCNC processes in the quark sector [27] and those ∆F = 1 rare K and B decays in which new physics contributions enter already at the tree level [44]. Short reviews of these results can be found in [78][79][80]. The analyses of processes with dipole operators like B → X s γ, µ → eγ, and electric dipole moments, where new physics enters first at the one-loop level will be presented elsewhere.…”
Section: Discussionmentioning
confidence: 93%